Instabilities in imperfect thick cones subjected to axial compression and external pressure - Ifayefunmi, Olawale; Blachut, Jan (Elsevier, 2013)
The paper presents results of a numerical study into the buckling resistance of geometrically imperfect mild steel cones subjected to: (a) axial compression only, (b) lateral external pressure only, and (c) axial compression and external pressure acting simultaneously. Initial geometric imperfections are taken in the form of the eigenmode, `a single wave’ extracted from the eigenmode and localized smooth dimple modelled analytically. Load carrying capacity of imperfect models is computed using the Finite Element proprietory code. Buckling strength of axially compressed and imperfect cone is only 55% of geometrically perfect model. Buckling strength of a cone subjected to lateral pressure, on the other hand, amounts to 43% of the corresponding value of perfect model. But it is the shrinkage of stability plot of imperfect cone which was found to be significant. For imperfect cones subjected to combined axial compression and external pressure, the collapse envelope shrinks by 48% with the elastic sub-set being reduced by 51%.